TRANSFORMASI PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL: TANTANGAN DAN PELUANG UNTUK GENERASI Z - Mohammad Firmansyah; Yulsiva Anissatun Nadhiroh; Ilzam Hubby Dzikrillah Alfani; Zaki Arrazaq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of Islamic Religious Education (PAI) in the digital era has become a necessity in facing technological developments and changes in the characteristics of students, especially Generation Z. This study aims to analyze the challenges and opportunities in the implementation of digital-based PAI, as well as to formulate strategies that can increase the effectiveness of religious learning in the modern era. The research method used is a literature review with a qualitative approach, which examines various academic sources, journals, books, and reports related to the development of digitalization in religious education. The results of the study show that the digitalization of PAI faces challenges such as minimal digital literacy among educators, limited access to technology for some students, and the potential for misuse of technology. However, there are also various opportunities, such as increasing accessibility of learning resources, the use of attractive interactive media, and the ease of personalizing learning according to the needs of students. The novelty of this study lies in the strategic analysis that highlights the importance of increasing digital competence for educators, developing adaptive technology-based curriculum, and optimizing digital platforms as a more inclusive and effective medium for Islamic preaching and education for Generation Z. Thus, the transformation of PAI in the digital era can be a more relevant means of forming character and contextual understanding of religion for the younger generation.